1996
DOI: 10.13031/2013.27564
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Characteristics of Ethyl and Methyl Ester of Rapeseed Oil Compared with Low Sulfur Diesel Control Fuel in a Chassis Dynamometer Test of a Pickup Truck

Abstract: Comprehensive tests were performed on an on-road vehicle in cooperation with the Los Angeles County Metropolitan Transit Authority emissions test facility. All tests were with a transient chassis dynamometer. Tests included both a double arterial cycle of 768 s duration and an EPA heavy duty vehicle cycle of 1,060 s duration. The test vehicle was a 1994 pickup truck with a 5.9-L turbocharged and intercooled, direct injection diesel engine. Rapeseed methyl (RME) and ethyl esters (REE) and blends were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…e pour point is the temperature below which the fuel will not �ow. As a result of this higher value, the performance of the biodiesel in cold conditions will be worse than that of petroleum diesel [10]. One of the most important characteristics of any fuel is its �ash point� this is de�ned as the lowest temperature at which it can vaporize to form an ignitable mixture in air.…”
Section: Analysis Of the Results From The Characterization Of Thementioning
confidence: 99%
“…e pour point is the temperature below which the fuel will not �ow. As a result of this higher value, the performance of the biodiesel in cold conditions will be worse than that of petroleum diesel [10]. One of the most important characteristics of any fuel is its �ash point� this is de�ned as the lowest temperature at which it can vaporize to form an ignitable mixture in air.…”
Section: Analysis Of the Results From The Characterization Of Thementioning
confidence: 99%
“…Peterson et al performed test, on a direct injected, four-cylinder John Deere 4329t-turbocharged diesel engine and investigated that the specific gravity of biodiesel was higher compared to diesel and viscosity of biodiesel was 1.9 times to that of diesel fuel at 40°C, heat of combustion for biodiesel was 12% lower than that of diesel fuel, the smoke opacity and engine power with use of biodiesel were lowered by 71% and 4.8% respectively when compared with diesel fuel, maximum engine torque was lowered by 6% and 3.2% at variable speeds of 1700rpm and 1300 rpm, respectively. However, no marginal differences between thermal efficiencies were recorded [6]. P.V Rao, performed experiments on a 3.72 kW, water cooled, direction injection engine having compression ratio of 16.5 and 1600 rpm engine speed and found that the ignition lag of KME blends was shorter and hence combust earlier in combustion chamber due to having higher cetane number than that of diesel fuel, the heat release rate (HRR) of KME blends was lower compared to diesel fuel due to having lower calorific value of KME oil [7].…”
Section: Introductionmentioning
confidence: 84%
“…Several reports show NO x is increased with biodiesel. However, in chassis dynamometer tests with the Cummins B 5.9 L, a reduction in NO x with a corresponding increase in PM was found [105,106]. The variability in NO x response for biodiesel may be due to individual variables in the engines themselves.…”
Section: Oxides Of Nitrogenmentioning
confidence: 94%